Neoadjuvant Ifosfamide and Epirubicin in the Treatment of Malignant Peripheral Nerve Sheath Tumors. (4th May 2017) - Hirbe, Angela C.; Cosper, Pippa F.; Dahiya, Sonika; Van Tine, Brian A.
Abstract : Background and Objectives. Malignant peripheral nerve sheath tumors (MPNSTs) are aggressive soft tissue sarcomas with poor overall survival. Response to chemotherapy has been debated for these tumors. Methods. We performed a retrospective analysis of the patients at our institution with a biopsy-proven diagnosis of MPNST that underwent neoadjuvant chemotherapy prior to surgery. Results. We retrospectively identified five patients who received neoadjuvant chemotherapy with epirubicin and ifosfamide that demonstrated a 30% reduction in tumor growth and a 60% response rate by RECIST criteria. Additionally, a metabolic response was observed in all three patients who received serial PET scans during neoadjuvant treatment. The clinical benefit rate, which includes stable disease, was 100%. Conclusions. Our data suggest that MPNSTs do respond to epirubicin and ifosfamide based chemotherapy and prospective studies are warranted to further define the clinical benefit.